An intervention study to improve primary school students' self-regulated strategy use in English writing through e-learning in Hong Kong. Issue 9 (8th December 2022) - Bai, Barry; Wang, Jing; Zhou, Huixuan
Abstract: The present study reports on the effects of a self-regulated (SRL) writing strategy-based intervention supported with e-learning tools on SRL strategy use in English writing with 468 Hong Kong primary school students. The changes to the students' motivation in English writing, and their e-learning acceptance were also measured. The study adopted a pretest and posttest design and the data was collected through a questionnaire, which consisted of three measures, i.e. SRL writing strategy use, motivation in English writing, and e-learning acceptance. The SRL writing strategy use measure included four types of strategies, i.e. planning, text-generating, monitoring, and revising. The motivation measure had two scales, i.e. interest and self-efficacy, and the e-learning acceptance measure included four scales, i.e. perceived usefulness, perceived ease of use, attitude and continuance intention. The intervention saw significant improvements on the students' use of all four types of SRL writing strategies. Positive changes also took place to one scale of motivation, i.e. interest, and three scales of e-learning acceptance, i.e. perceived usefulness, attitude and continuance intention. There was no significant improvement to self-efficacy and perceived ease of use. Additionally, the correlations between all the scales became stronger after the intervention. Important implications for teaching ESL/EFL writing through e-learning are drawn.